The Importance of Action Games in the Normative Activity of the Heart and Vascular System - Asqar Shamuratov (Bright Mind Publishing, 2025)
This article examines the importance of physical education in preschool institutions in our country. The tasks of physical education in preschool institutions are highlighted.
Keywords: Physical education, physical training, preschool education, education, upbringing, health improvement, task, training, exercise.